ROASTING OF NICKEL HYDROCARBONATE (Conferencea, 2022)
Thermal treatment of finely dispersed materials with particles smaller than 50 μm by the convective method of heat supply is notrationally, since there is a significant entrainment of particles of the processed material by the flow of the drying agent and the required dust-collecting equipment is bulky and inefficient, resulting in environmental pollution. In addition, the amount of heat input in such devices is usually limited due to convective heat transfer, but also due to an insufficiently developed heat supply surface.